2020
DOI: 10.1177/1078345820953154
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Experiences of Care Provision in the Correctional Setting: A Scoping Review

Abstract: Little is known about the experiences of correctional health care providers and how their experiences impact the correctional health care system. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols guidelines, multiple databases were searched. Each abstract was read by two reviewers with a third for consensus as needed. Full-text articles were selected through a second round of review. Of 4,467 citations, 61 were selected for full-text evaluation and 23 were ultimately in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…While mistrust between incarcerated patients and correctional health care professionals may be common, we do not intend to discount the efforts of correctional health care professionals, who often are disempowered, practicing in a setting that undermines patient trust, and whose recommendations for patient care may be stymied by forces out of their control. 10 …”
Section: Community Clinicians Should Re-address Incarcerated Patient’s Goals Of Carementioning
confidence: 99%
“…While mistrust between incarcerated patients and correctional health care professionals may be common, we do not intend to discount the efforts of correctional health care professionals, who often are disempowered, practicing in a setting that undermines patient trust, and whose recommendations for patient care may be stymied by forces out of their control. 10 …”
Section: Community Clinicians Should Re-address Incarcerated Patient’s Goals Of Carementioning
confidence: 99%
“…Prior to the COVID-19 pandemic, published reviews related to nurses and other health professionals working in correctional facilities identified occupational stressors including security prioritization, conflicts, fear, job demands [ 11 ], burnout, stress [ 12 ], and secondary trauma [ 13 ]. Within North America, older U.S. studies have demonstrated moderate [ 14 ] and high [ 15 ] work-related mean stress levels among correctional nurses.…”
Section: Introductionmentioning
confidence: 99%